2017
DOI: 10.1002/jbm.a.36214
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydroxyapatite nanoparticles on mechanical behavior and biological performance of porous shape memory polyurethane scaffolds

Abstract: Abstract:The scaffold which provides space for cell growth, proliferation, and differentiation, is a key factor in bone tissue engineering. However, improvements in scaffold design are needed to precisely match the irregular boundaries of bone defects as well as facilitate clinical application. In this study, controllable three-dimensional (3D) porous shape memory polyurethane/nano-hydroxyapatite (SMPU/nHAP) composite scaffold was successfully fabricated for bone defect reparation. Detailed studies were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 20 publications
0
34
0
3
Order By: Relevance
“…Composite scaffold bearing HAp NPs have shown different mechanical properties which mainly depend on the nature of composite and preparation method. Incorporation of HAp NPs has been reported to increase modulus of compression in the porous shape memory polyurethane (Yu et al, 2018) or enhance the ultimate compressive strength in PCL/poly(lactic-co-glycolic acid) (PLGA)/HAp NPs (Li X. et al, 2017). In another study compressive modulus of gelatin HAp NPs composite hydrogel has been shown to decrease by increasing the weight percentage of HAp NPs.…”
Section: Ceramic Nanoparticlesmentioning
confidence: 99%
“…Composite scaffold bearing HAp NPs have shown different mechanical properties which mainly depend on the nature of composite and preparation method. Incorporation of HAp NPs has been reported to increase modulus of compression in the porous shape memory polyurethane (Yu et al, 2018) or enhance the ultimate compressive strength in PCL/poly(lactic-co-glycolic acid) (PLGA)/HAp NPs (Li X. et al, 2017). In another study compressive modulus of gelatin HAp NPs composite hydrogel has been shown to decrease by increasing the weight percentage of HAp NPs.…”
Section: Ceramic Nanoparticlesmentioning
confidence: 99%
“…The apparent density and porosity of PU foam and PU-HA scaffolds were calculated by Equations (1) to (3). 21 Moreover, BET analysis (BEL, BELSORP MINI II) was performed to investigate the nanopores in the samples.…”
Section: Characterizationmentioning
confidence: 99%
“…The shifting of the peaks at 1012, 1223, and 3401 cm −1 in PU foam up to 1026, 1228 and 3409 cm −1 in PU-HA scaffolds, respectively, can be assigned to physical and/or chemical interactions [48][49][50] between HA and PU/ PU monomers ( Figure 5). Physical interaction may include hydrogen bonding between ─NH in urethane linkage, 17,21 and phosphate group and hydroxyl group in HA, hydrogen bonding between ether oxygen 51 in the soft segment F I G U R E 4 FTIR spectra of HA powder, PU foam and PU-HA scaffolds for a wavenumber region of (a) 400-4000 cm −1 , (b) 400-2000 cm −1 . FTIR, Fourier-transform infrared; PU, polyurethane [Color figure can be viewed at wileyonlinelibrary.com] (polyol) of PU and hydroxyl group in HA, metal affinity between ─C=O in urethane linkage and Ca 2+ in HA.…”
Section: Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Nano-hydroxyapatite (nHA) is the main inorganic calcium phosphate mineral component of bones and teeth. The close chemical similarity of nHA to natural bone has led to extensive research efforts to use synthetic nHA as a bone substitute [ [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. More than twenty years ago, Yamasaki et al showed that, after nHA ceramics were implanted into nonosseous sites of dogs for 3 months, the micropores of the porous nHA ceramics were found full of eosinophilic amorphous substance, suggesting a bone matrix [ 16 ].…”
Section: Introductionmentioning
confidence: 99%